Nutritional status vis-a-vis iodine deficiency in children of "Save Our Soul"children’s village in rural Varanasi: a micro-level study - Majhi, Madan M.; Mishra, Chandra P.; Shankar, Prem; Khanam, Zoobi (International Journal of Research in Medical Sciences, 2017)
Background: There is paucity of data with regard to the Iodine deficiency in an organized sector like SOS children’s village which is an independent, non-governmental, social development organization located in urban Varanasi. Uttar Pradesh is one of the endemic states for goiter. It is expected that similar situation of goiter may prevail in children as well. It is a matter of concern that micro nutrient deficiency and under-nutrition may exist side by side. The objectives of the study were to assess nutritional status and find out the extent of Iodine deficiency in the study subjects, to find out the association between under nutrition and Iodine deficiency and to find out the Iodine content of salt used for cooking in the family. Methods: 118 children of age group 6 to 15 years, from a Non-Governmental Organization (Save Our Soul) in Rural Varanasi constituted materials of the study. Consent from the director of the institution and assent from the individual children was taken prior to examination. All the subjects were examined clinically for the Presence of Goiter. They were subjected to weight and height recording following standard technique. Salt samples from the houses were tested by spot Iodine detection kit. Results: In case of 72.6% female and 91.3% male subjects, BMI for age was <100% of the respective reference values; in all 76.3% subjects belonged to this category. Presence of Goiter among male children was 34.7% and among female children it was 22.2% and overall it was 24.6%. Significant association was observed between nutritional status and iodine deficiency (p<0.05). In 37.5% of salt samples, iodine content was 7 ppm and rest 62.5% shows iodine content 15ppm. Conclusions: Nutritional status of the children under reference was far from being satisfactory. High prevalence of Goiter is matter of serious concern. Iodized salt consumption in the houses was up to the mark but Iodine content of the salt samples from houses was not satisfactory.